2019
DOI: 10.3389/fmicb.2019.01432
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Genes Associated With Newcastle Disease Virus Load in Chick Embryos From Inbred and Outbred Lines

Abstract: Newcastle disease virus (NDV) causes substantial economic losses to smallholder farmers in low- and middle-income countries with high levels of morbidity and mortality in poultry flocks. Previous investigations have suggested differing levels of susceptibility to NDV between specific inbred lines and amongst breeds of chickens, however, the mechanisms contributing to this remain poorly understood. Studies have shown that some of these differences in levels of susceptibility to NDV infection may be accounted fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…The small proportion of shared DEGs between the current study and previous studies, as well as the opposite regulation of 17 shared significant pathways predicted by IPA suggest quite different response to NDV in different tissues or chicken lines. This is consistent with the previous reports about tissue-specific immune response [ 46 ] and distinct immune gene expression between different chicken breeds [ 47 ]. Maternally transferred antibody may also be a contributing factor to gene expression differences among studies.…”
Section: Discussionsupporting
confidence: 93%
“…The small proportion of shared DEGs between the current study and previous studies, as well as the opposite regulation of 17 shared significant pathways predicted by IPA suggest quite different response to NDV in different tissues or chicken lines. This is consistent with the previous reports about tissue-specific immune response [ 46 ] and distinct immune gene expression between different chicken breeds [ 47 ]. Maternally transferred antibody may also be a contributing factor to gene expression differences among studies.…”
Section: Discussionsupporting
confidence: 93%
“…response to NDV in different tissues or chicken lines. This is consistent with the previous reports about tissue-specific immune response [36] and distinct immune gene expression between different chicken breeds [37]. Maternally transferred antibody may also be a contributing factor to gene expression differences among studies.…”
Section: Discussionsupporting
confidence: 93%
“…Bobbo et al (2013) reported differences in immune response to NDV between Nigerian local chicken phenotypes. In a study by Schilling et al (2019) , three main Tanzanian local chicken ecotypes responded to NDV infection differently, with the Ching'wekwe recording the lowest viral load, followed by Kuchi and then Morogoro Medium, which had the highest viral load. Adeyemo et al (2012) also reported that in Nigeria Yoruba ecotype chickens had higher immune response to NDV, followed by the Fulani ecotype, and then the exotic breed.…”
Section: Discussionmentioning
confidence: 99%